ANALYSIS OF OPPORTUNITIES AND CHALLENGES OF 30% FEMALE REPRESENTATION IN THE LEGISLATURE: PERSPECTIVES FROM JOHN RAWLS' THEORY OF JUSTICE - I Nyoman Gian Erlangga (Transpublika Publisher, 2024)
This research aims to explore the possibilities of achieving a 30% representation of women in the legislature through the lens of John Rawls' theory of justice. Additionally, it examines the challenges faced in implementing this representation. The research adopts a normative legal research approach. In essence, Citizens share the same basic rights, one of which is the right to elect and vote. The Election Law regulates the 30% women's representation in the legislature, and efforts are being made to promote and protect women's rights in this regard. These efforts align with Rawls' concept of maximum freedom, which emphasizes that individual rights should not be compromised for the sake of society or the state. However, obstacles persist in achieving the 30% women's representation in the legislature, primarily due to the prevailing patriarchal culture in society. Rawls suggests that non-violent political means can be employed to challenge and overcome such injustices. Implementing affirmative policies is one effective approach to combat the patriarchal culture and promote gender equality.